Emotional Dynamics of The Fourth Semester Students During Online Learning in English Department University of Mataram - Muhammad Amin; Amaliya Putri; Lalu Thohir (Indonesian Journal of Teacher Education, 2023)
For the past two years, we have lived with the COVID-19 virus, which has been infecting humans for almost two years. The COVID-19 have resulted in the widespread disruption such as travel restrictions, closure of schools, global economic recession, political conflicts. This study aimed to know how student emotions develop over time and what causes students to experience positive and negative emotions during online learning. This type of research is a qualitative descriptive method. This research involved 70 students in the fourth semester at the University of Mataram. Data collection was carried out by interviews and questionnaires. Then, the data analysis procedures in this study include data reduction, data presentation, and drawing conclusions. These results suggest that the emotional development of students while engaging in online learning occurs and that the emotional dynamics experienced by students tend to be positive. They are happy because online learning can be done flexibly and causes of the positive and negative emotions that students have during the online learning process. It can be concluded that students experience more negative emotions due to an unstable internet network and limited internet quota. Only a few students felt positive emotions when they understood the subject matter delivered by the lecturer; At that time students feel happy and proud of their abilities